A formação do protagonismo do jovem rural a partir da pedagogia da alternância em casas familiares rurais - Borges, Graziela Scopel (2012)
Thinking in youth as actors-subjects capable of participating in a more effective way of social change, is to think of a way to enhance the opportunities for endogenous development. The theme of juvenile protagonism has been discussed in recent years as a way of encouraging the involvement of young and learning as a form of democratic participation. This dissertation research has as its theme the study of practices pedagogical in the Pedagogy of Alternating of Rural Family Houses and formation for the protagonism of rural youth. We conducted a social search of qualitative character, with the data collection instrument observations, questionnaires and interviews. Was use of the instruments of the Pedagogy of Alternating as a methodological option of directing research. It was understood that juvenile protagonism is inherent in the pedagogical Pedagogy of Alternating and teaching tools that foster the formation of the rural youth protagonism. It should be taken into account in this context, the contradictions of pedagogical practices and the different socio-cultural contexts to which the Rural Family Houses are inserted. It was felt that rural youth needs more social media channels and spaces of participation, especially in rural communities. Initiatives to ensure and at times foster protagonism of rural youth were identified and highlighted as actions that were beyond the youth activism.